PEMBERDAYAAN PENDIDIKAN ISLAM SEBAGAI UPAYA PENGENTASAN KEMISKINAN - Armoyu, H. Moh (IAIN Ponorogo, 2013)
Abstract: The problem of poverty has happened for long times and it seems to be more complicated and endless matter. Because of poverty, many children cannot proceed to study and even they should work to help parents earn for living. Therefore, it needs high effort and commitment to overcome this problem and it should be done deliberately and continuously. This study attempted to investigate the role of education in poverty alleviation in Indonesia. The data was collected by employing in-depth interviews and analyzed using phenomenological models. The results showed that: ( 1 ) the level of education could cut the chain of poverty; ( 2 ) in general, the results of this study found that there were a foster care program for children from economically-challenged families,Â educational empowerment that emphasizes children from economically-challenged families as a central point of empowerment in the development process, and providing opportunity for talented children from economically-challenged families to proceed higher study inÂ reputable universities, (3) conducting research to select students who will be given a scholarship, based on academic experience and the background of parents. Â ÙÙ Ø¯ÙØ§ÙÙØ£Ø§ ÙÙ ÙØ±Ø«Ù Ø³Ø±Ø¯Ù ÙØ§ Ø±ÙÙÙØ§ Ø¨Ø³Ø³Ø¨ .Ø©ÙØ§ÙÙÙØ§ Ø§ÙÙ Ø³ÙÙ ÙØ£ÙÙ Ø¯ÙØ¹ÙØ§ Ø©ÙÙ Ø¯Ù Ø©ÙØ¶Ù Ø±ÙÙÙØ§ Ø©ÙØ¶Ù :ØµØ®ÙÙ Â ÙØµØ§ÙØªÙÙ Ø§ ÙØ¹Ø§Ù ÙØ¬Ø§ Ù Ø²Ø¹ÙØ§ Ø¯ÙØ¬Ù ÙÙ Ø¯Ø¨ÙØ§ Ø§Ø°Ù .Ø´Ø§Ø¹ÙÙ Ø§ ÙÙØ¹ ÙÙØµØÙÙ )ÙÙÙÙ Ø¹Ù( Ù ÙØ¡Ø§Ø¨Ø¢ ÙÙØ¯Ø¹Ø§Ø³Ù ÙØ¨ Ø³Ø±Ø§Ø¯ÙÙ Ø§Â Ù ÙØ¯ÙØª ÙÙ Ù ÙØ³ÙÙ Ø±ÙÙÙØ§ Ø©ÙØ¶Ù ÙÙØ¹ Ø¡Ø§Ø¶ÙÙØ§ ÙÙÂ Ø©ÙØ¨ØªØ±ÙØ§ Ø±ÙØ¯ ÙÙ Ø«ØØ¨ÙØ§ Ø©Ø³Ø§Ø±Ø¯ÙØ§ ÙØ°Ù ØªÙÙØ§Ø .Ø©ÙÙØ´ÙÙ Ø§ ÙØ°Ù ÙÙØÂ Ø©ÙØ¨Ø§ÙÙÙ Ø§ ÙÙØ±Ø· ÙØ¹ Ø§ÙØªØ§ÙØ§ÙØ¨ Ø¹Ù ØªØ¬Ù Ø§ÙØ³ÙÙÙØ¯ÙØ¥ ÙÙ Ø«ØØ¨ÙØ§ Ø§Ø°Ù ÙØ±ØØ£ .Ø©ÙØ¨ØªØ±ÙØ§ ÙÙØ±Ø· ÙØ¹ Ø±ÙÙÙØ§ Ø©ÙØ¶ÙÙ ÙÙØØ§ ÙØ¨Ø³Â ÙÙØ¨ØªØ±ÙØ§ ÙÙØªØ³ÙÙ Ø§ ÙØ£ )1 : ÙÙØ¹ Ø«ØØ¨ÙØ§ Ø¬Ø¦Ø§ØªÙ ØªÙØ¯ . ÙØ¬ÙÙÙÙÙ ÙÙÙÙÙØ§ ÙÙÙØØªÙØ§Ø¨ ÙÙÙÙØªØ Ø¨ÙÙØ³Ø£ Ø§Ù Ø£Ù ØØ©ÙÙÙ Ø¹ÙØ§Â Ø©Ø³Ø§Ø±Ø¯ÙØ§ ÙØ¹ ÙÙØ¹Ø·ÙÙÙÙ Ø§ Ø¯ÙØ§ÙÙØ£Ø§ ÙÙØ¶ØªØ Ø¬Ù Ø§ÙØ±Ø¨ ÙØ§ÙÙ ÙØ£ ÙÙØ¹ Ø©Ø³Ø§Ø±Ø¯ÙØ§ ØªÙØ¯ Ø©Ù Ø§Ø¹Ù )2 ØØ±ÙÙÙØ§ Ø©ÙØ³ÙØ³Ù Ø¹Ø·Ø§ÙÂ Ù Ø§ÙÙÙØ§ )3 ØØ©ÙÙÙ Ø¯Ø§ÙÙØ£Ø§ Ù ÙØªØ§Ø±Ø¯Ù Ø©ÙÙ ÙØªÙ Ø©Ù Ø¯ÙØªÙÙ Ø§ ØªØ§Ø¹Ù Ø§ÙØ¬Ø§ ÙØ£ Ø³Ø±Ø§Ø¯ÙÙ Ø§ ÙÙ Ù ÙÙØ§Ø®Ø¯ÙØ¥ Ø©ÙÙØ§ÙÙ ØØ§Ù Ø©ÙØ±ÙÙÙØ§ Ø±Ø³ÙØ£Ø§ ÙÙ Â Ù ÙØ¦Ø§Ø¨Ø¢ Ø©ÙÙÙØ®Ù Ø©ÙÙÙ Ø¯Ø§ÙÙØ£Ø§ Ù ÙØ§Ø¨Ø±Ø® Ø¨Ø³Ø Ø©ÙØ³Ø§Ø±Ø¯ÙØ§ Ø©ØÙÙÙ Ø§ ÙÙØ¹ ÙÙÙØµØÙØ³ ÙÙØ°ÙØ§ Ø¨ÙØ§Ø·ÙØ§ ÙØ§ØªØ¬ ÙÙÙØ¯ ÙÙÙØØªØ¨Â Ù ÙØªØ§ÙÙ Ø£ÙKeywords: Pemberdayaan, pengentasanÂ kemiskinan,Â pendidikan Islam.